Validation pharmaceutique des ordonnances : simulation à l’occasion d’un colloque de gestion pharmaceutique - Dubois, Sophie; Atkinson, Suzanne; Thibault, Maxime; Bussières, Jean-François (Pharmactuel, 2016)
-